Factors influencing Malaysian students' choice of diploma programs: analysing their interrelation with interest and satisfaction / Nor Hazizah Julaihi and Mohammad Isa Mohamadin - Julaihi, Nor Hazizah; Mohamadin, Mohammad Isa (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This study explores the factors influencing the choice of diploma programs among undergraduate students at Universiti Teknologi MARA (UiTM), Sarawak Branch, Malaysia, and their interrelation with interest and satisfaction. Data were collected from 715 first- semester diploma students across three UiTM Sarawak campuses during the October 2023 – February 2024 session, via a questionnaire. The findings highlight the significant impact of personal decisions and family influence in shaping students' choices of diploma programs. Employment opportunities, career aspiration, and academic qualifications emerged as the most influential factors. Nonetheless, students who enrolled in their first-choice programs report high satisfaction, demonstrating that strong interest plays a crucial role in fostering a positive educational experience. Additionally, intrinsic factors are the most significant determinants of students' interest and satisfaction, while extrinsic factors significantly influence interest but have a lesser impact on satisfaction. In contrast, interpersonal factors were found to have minimal effect. This study establishes a comprehensive conceptual model explaining the factors influencing students in choosing their diploma programs and their interrelation with interest and satisfaction. It highlights the importance of intrinsic and extrinsic factors in educational decision-making and suggests that a supportive environment enhances satisfaction and educational outcomes. The insights can inform policies to enhance student experiences and support informed programs choices in higher education. At the same time, they can contribute to ensure inclusive and equitable quality education, in alignment with Sustainable Development Goal 4 (SDG4), which promotes lifelong learning opportunities for all.